IgG4-related disease in Italy: clinical features and outcomes of a large cohort of patients. (3rd March 2016) - Campochiaro, C; Ramirez, GA; Bozzolo, EP; Lanzillotta, M; Berti, A; Baldissera, E; Dagna, L; Praderio, L; Scotti, R; Tresoldi, M; Roveri, L; Mariani, A; et al.
Abstract : Objectives : To describe the clinical features, treatment response, and follow-up of a large cohort of Italian patients with immunoglobulin (Ig)G4-related disease (IgG4-RD) referred to a single tertiary care centre. Method : Clinical, laboratory, histological, and imaging features were retrospectively reviewed. IgG4-RD was classified as 'definite' or 'possible' according to international consensus guidelines and comprehensive diagnostic criteria for IgG4-RD. Disease activity was assessed by means of the IgG4-RD Responder Index (IgG4-RD RI). Results : Forty-one patients (15 females, 26 males) were included in this study: 26 with 'definite' IgG4-RD and 15 with 'possible' IgG4-RD. The median age at diagnosis was 62 years. The median follow-up was 36 months (IQR 24–51). A history of atopy was present in 30% of patients. The pancreas, retroperitoneum, and major salivary glands were the most frequently involved organs. Serum IgG4 levels were elevated in 68% of cases. Thirty-six patients were initially treated with glucocorticoids (GCs) to induce remission. IgG4-RD RI decreased from a median of 7.8 at baseline to 2.9 after 1 month of therapy. Relapse occurred in 19/41 patients (46%) and required additional immunosuppressive drugs to maintain long-term remission. Multiple flares occurred in a minority of patients. A single case of orbital pseudotumour did not respond to medical therapy and underwent surgical debulking. Conclusions : IgG4-RD is an elusive inflammatory disease to be considered in the differential diagnosis of isolated or multiple tumefactive lesions. Long-term disease control can be achieved with corticosteroids and immunosuppressive drugs in the majority of cases.